The so-called nonsense inscriptions on Ancient Greek vases between Paideia and Paidiá - Chiarini, Sara. (Brill Studies in Greek and Roman Epigraphy, 2018)
As the first extensive survey of the ancient Greek painters' practice of writing nonsense on vases, The So-called Nonsense Inscriptions on Ancient Greek Vases by Sara Chiarini provides a systematic overview of the linguistic features of the phenomenon and discusses its forms and contexts of reception. While the origins of the practice lie in the impaired literacy of the painters involved in it, the extent of the phenomenon suggests that, at some point, it became a true fashion within Attic vase painting. This raises the question of the forms of interaction with this epigraphic material. An open approach is adopted: "reading" attempts, riddles and puns inspired by nonsense inscriptions could happen in a variety of circumstances, including the symposium but not limited to it.